Pengaruh Literasi Keuangan, Inklusi Keuangan, dan Kontrol Diri Terhadap Perilaku Menabung Pada Masyarakat Generasi Z di DKI Jakarta - Qurotul Aini; Karuniana Dianta A.S; Aditya Pratama (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
The purpose of this study is to analyze "The Effect of Financial Literacy, Financial Inclusion, and Self-Control on Saving Behavior (Case Study of Generation Z Communities in DKI Jakarta)". The problem that often occurs is that generation Z usually uses their income only for consumption and not for saving. The method used in this research is quantitative. This study uses Primary data by distributing questionnaires through Google forms distributed on social media. The tests used in this study are prerequisite analysis test, multiple linear regression test and hypothesis testing. The results of this study explain that financial literacy affects saving behavior, financial inclusion has no effect on saving behavior, self-control affects saving behavior, and financial literacy, financial inclusion, and self-control have a simultaneous or joint effect on saving behavior.